2014 summer Arctic sea ice thickness and concentration from shipborne observations. Issue 8 (3rd August 2019) - Wang, Qingkai; Li, Zhijun; Lu, Peng; Lei, Ruibo; Cheng, Bin
ABSTRACT: A series of shipborne sea ice observations were performed during the Chinese National Arctic Research Expedition in the Pacific Arctic sector between 2 August 2014 and 1 September 2014. Undeformed sea ice thickness (SIT) as well as area fractions of open water, melt pond, and sea ice ( A w, A p, and A i ) were monitored using downward-oriented and oblique-oriented cameras. The results show that SIT varied between 20 and 220 cm throughout the whole cruise, with the average and standard deviation equaling 104.9 and 29.1 cm, respectively. Mean A w and A i were 0.52 and 0.44 in the marginal ice zone, respectively, while mean A w decreased to 0.23 and mean A i increased to 0.73 in the pack ice zone. Limited variation between 0 and 0.32 in A p was seen throughout the whole cruise. Shipborne sea ice concentration was then rectified and mapped across a large transect to validate estimates derived from the satellite sensors Special Sensor Microwave Imager/Sounder (SSMIS) (25 km) and AMSR2 (25 km). Overestimations were 9.5% and 9.9% for SSMIS and AMSR2 compared with measurements, respectively. The mean areal broadband surface albedo based on shipborne survey increased from 0.07 to 0.66 along the transect between 72°N and 81°N.